Can citrate efflux from roots improve phosphorus uptake by plants? Testing the hypothesis with near‐isogenic lines of wheat. Issue 3 (24th February 2014) - Ryan, Peter R.; James, Richard A.; Weligama, Chandrakumara; Delhaize, Emmanuel; Rattey, Allan; Lewis, David C.; Bovill, William D.; McDonald, Glenn; Rathjen, Tina M.; Wang, Enli; Fettell, Neil A.; Richardson, Alan E.
<x xml:space="preserve">Abstract</x> Phosphorus (P) deficiency in some plant species triggers the release of organic anions such as citrate and malate from roots. These anions are widely suggested to enhance the availability of phosphate for plant uptake by mobilizing sparingly‐soluble forms in the soil. Carazinho is an old wheat (Triticum aestivum) cultivar from Brazil, which secretes citrate constitutively from its root apices, and here we show that it also produces relatively more biomass on soils with low P availability than two recent Australian cultivars that lack citrate efflux. To test whether citrate efflux explains this phenotype, we generated two sets of near‐isogenic lines that differ in citrate efflux and compared their biomass production in different soil types and with different P treatments in glasshouse experiments and field trials. Citrate efflux improved relative biomass production in two of six glasshouse trials but only at the lowest P treatments where growth was most severely limited by P availability. Furthermore, citrate efflux provided no consistent advantage for biomass production or yield in multiple field trials. Theoretical modeling indicates that the effectiveness of citrate efflux in mobilizing soil P is greater as the volume of soil into which it diffuses increases. As efflux from these wheat plants is restricted to the root apices, the potential for citrate to mobilize sufficient P to increase shoot biomass may be limited. We conclude that Carazinho has other attributes that contribute to its comparatively good performance in low‐P soils.